Determinants of Marital Satisfaction from Married Individuals’ Perspectives in Addis Ababa: A Qualitative Study - Wondimu, Shimelis; Andualem, Tamirie (International Journal of Qualitative Research, 2024)
Studies have identified various factors that determine marital satisfaction. However, there is still a scarcity of studies that focus on the factors influencing marital satisfaction. Most previous studies have focused on deficit factors rather than strengthening factors, indicating a knowledge gap regarding factors that positively contribute to marital satisfaction. This study aimed to identify the factors influencing marital satisfaction from the perspective of married individuals in Addis Ababa, Ethiopia. Semi-structured interviews and focus group discussions (FGDs) were used as data collection techniques. The data was collected from 15 participants. The study uncovered key factors that contribute to marital satisfaction. The findings include views about marriage, readiness for marriage, caring behavior, integrity, patience, and religiousness. Marriage practitioners, policymakers, and social workers could benefit from this study. The limitations and future directions were also discussed.